Analysis of essential oil from leaves and Bulb of Allium atroviolaceum - Sebtosheikh, Parniyan; Qomi, Mahnaz; Ghadami, Shima; Mojab, Faraz (International Pharmacy Acta, 2020)
Background and objective: Medicinal plants used in traditional medicine as prevention and treatment of disease and illness or use in foods, has a long history. Plants belonging to genera Allium have widely been acquired as food and medicine. In many countries, including Iran, a variety of species of the genus Allium such as garlic, onions, leeks, shallots, etc use for food and medicinal uses. Method: The leaves and bulbs of Allium atroviolaceum, collected from Borujerd (Lorestan Province, Iran) in May 2015 and their essential oils of were obtained by hydro-distillation. The oils were analyzed by gas chromatography coupled with mass spectrometry (GC/MS) and their chemical composition was identified. Results: The major constituents of A. atroviolaceum leaves oil were dimethyl trisulfide (59.0%), ethyl linolenate (12.4%), phytol (11.4%) and in bulb oil were methyl methyl thiomethyl disulfide (61.3%), dimethyl trisulfide (15.1%) and methyl allyl disulfide (4.3%). The major constituents of both essential oils are sulfur compounds. Conclusion: The results of the present study can help to increase of our information about composition of an edible herb in Iran. The major components of the oils can use as marker for standardization of the herbs.